Financial Management Strategy Of UMKM In Syirkah Berkah Bersama Cooperative Sidoarjo - Aini, Nurul; Marpurdianto, Kharis; Pradika, Novaldy Arief (Doktoral Ilmu Manajemen, Universitas Pasundan, 2024)
This study aims to analyze the financial management strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in the Syirkah Berkah Cooperative, Sidoarjo. In the context of the Indonesian economy, MSMEs have a very important role in creating jobs and contributing to Gross Domestic Product (GDP). However, many MSMEs face challenges in financial management that can hinder business growth and sustainability. This study uses a qualitative approach with a case study method, where data is collected through in-depth interviews with MSME owners and direct observation of the financial management practices implemented. The results of the study indicate that although many MSMEs in the Syirkah Berkah Cooperative still use simple financial recording methods, they have implemented several effective financial management strategies. These strategies include good budget planning, routine transaction recording, and cost control to improve efficiency. In addition, this study also identifies the need for further training on financial management and better access to financial information. Thus, this study makes an important contribution to understanding how financial management strategies can help MSMEs in the Syirkah Berkah Cooperative to improve financial resilience and support local economic growth. It is hoped that the results of this study can be a reference for business actors and researchers in the field of MSME financial management in Indonesia.